ANALISIS PENERIMAAN MASYARAKAT TERHADAP APLIKASI MAGELANG CERDAS PEMERINTAH KOTA MAGELANG DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Redha Fadhilah, Muthia; Hanani, Retna; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2024)
Magelang Cerdas application is an application owned by the Magelang City government. Even though it has won several awards, only a few people have downloaded the application. This research aims to determine the influence of perceived usefulness, perceived ease of use on user acceptance of the Magelang Cerdas application. The data collection technique was carried out by filling out a questionnaire by 100 respondents, where the respondents were residents of Magelang City who had never used the Magelang Cerdas application. The analysis techniques used are validity tests, reliability tests, and regression tests. Based on the research results, the following conclusions can be drawn: 1) There is an influence between perceived usefulness on user acceptance of the Magelang cerdas application (2) There is an influence between perceived ease of use on user acceptance of the Magelang cerdas application (3) There is an influence between perceived ease and perceived usefulness on acceptance Magelang cerdas application users. Efforts made by the Magelang City Government include increasing responses to reports, completing tourism information, increasing the simplicity of instructions, continuing to make updates so that the public can be more accepting of the Smart Magelang application.